Public Perception of the TikTok Application (A Qualitative Descriptive Study of the TikTok Application on Teenagers in Surakarta) - Rio Aldi Permana; Renty Yuniarti (Communigate, 2025)
The rapid development of social media has significantly transformed communication, making it easier, faster, and more accessible for users. This evolution has prompted social media platform providers to continuously innovate, creating diverse applications that serve as intermediaries for communication. One of the most prominent platforms today is TikTok, which has gained immense popularity globally, particularly among teenagers in Indonesia. Given its widespread usage, it is crucial to understand how adolescents perceive this social media application, and whether their perceptions are predominantly positive or negative. This study aims to explore public perceptions of TikTok among teenagers in Surakarta, focusing on the impact of social media content on adolescent psychological development. A qualitative research design with a descriptive approach is employed to capture the nuanced attitudes, opinions, and experiences of the participants. Data were collected through interviews, observations, and literature review to provide a comprehensive understanding of adolescents’ responses to the TikTok platform. The findings indicate that teenagers are particularly sensitive to negative content on TikTok, which can have detrimental effects on their psychological and emotional development, including issues related to self-esteem, behavior, and social interactions. While TikTok also offers opportunities for creativity and social engagement, negative influences appear more pronounced among adolescent users. This research contributes to the understanding of social media’s psychological impact on teenagers and provides insights for parents, educators, and policymakers to develop strategies that mitigate harmful effects while promoting positive use of digital platforms.